(untitled) (Alternautas, 2022)
Wampis leaders insist that nonhumans have always been central for territorial defence, even though this was not acknowledged publicly or in written form. Instead, they used the conservationist language of “protecting nature, forest and climate” as placeholder for the care of relationships with nonhumans. The change to an explicit invocation came with the realisation that to support their claim for the integral territory, a legal fundament based on ancestral usage and practices was needed. Going beyond the horizontal dimension of territoriality, the underground and the wider atmosphere became increasingly important in the context of oil and mining projects as well as for conservationist and carbon offset schemes. In this manner, indigenous leaders’ mediation and translations between ontological features and global eco-political discourses prepared the ground for an emergent eco-autonomy that includes what I call ‘vertical territoriality’.